STUDY THE EFFECT OF CYTOKININS AND AUXINS IN THE COMPOSITION AND PRODUCTION OF IN VITRO PLANTLETS HIPPEASTRUM HYBRIDUM - & Salman, Al-Amery (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The First Part of this study was conducted in the Plant Tissue Culture Lab at the College of Science, University of Nahrain from October 2014 to February,2015. The experiment was then completed in the Plant Tissue Culture Lab at the College of Agriculture, University of Baghdad From February 2015 to September 2015. Examine the possibility of using the tissue culture technique in the propagation of Hippeastrum hybridum. Explants (Bulbs, Leaves) had been sterilized using four different NaOCL concentrations: % 4.0, 2.0, 1.0, 0.0. After sterilization, explants were cultured on MS media supplemented with BA at four concentrations (2.0, 1.0, 0.5, 0.0 mg.liter-1) and NAA at four concentrations (0.5, 0.3, 0.1, 0. 0 mg.liter-1) to obtain plantlets. Afterwards, plantlets were moved to new MS media supplemented with BA (2.0, 1.0, 0.5, 0.0 mg.liter-1) and with or without four concentrations of NAA (0.5, 0.3, 0.1, 0.0 mg.liter-1) to enhance shoot proliferation. The resulted shoots from the best proliferation-enhance media were divided into two parts the first part was transferred to root-promoting media which also included two experiments where the first experiment was by transferring the shoots to MS media (half and full strength) supplemented with NAA at four concentrations (0.5, 0.3, 0.1, and 0.0 mg.liter-1). The second experiment included the best resulted shoots from the first experiment in addition to (0 and 2 mg.liter-1) actived charcoal to increase root percentage, root count, and root length.The resulted plants were acclimatized using peatmoss/soli mixture at the ratio of 1:1, 2:1, and 1:2 to obtain high surviving ratio. Results showed that the best explant(Bulbs, Leaves) was soaking in 3% NaOCl for 10 min. the results also showed that the leaves gave best response 90% when using MS media supplemented with 1.0 mg.liter-1 BA and 0.3 mg.liter-1 NAA when compared with the bulbs that showed low response profile. Furthermore, the best shoot proliferation media was MS supplemented with 1.0 mg.liter-1 BA and 0.3 mg.liter-1 NAA which resulted in 8.30 shoots.plant-1. The best rooting percentage was obtained when culturing the shoots in half strength MS media supplemented with 0.5 mg.liter-1 NAA with the existence of activated charcoal. The surviving percentage reached 95% when using the previously mentionedpeatmoss-soil/mixtures.